Inflammatory bowel disease activity threatens ankylosing spondylitis: implications from Mendelian randomization combined with transcriptome analysis - Ding, Yimei; Chen, Jiaxu; Li, Rouxin; Xue, Luan (Frontiers in Immunology, 2024)
Background: Inflammatory bowel disease (IBD) and ankylosing spondylitis (AS) share common traits of chronic recurrent inflammation affecting both the intestines and joints. Epidemiological studies have revealed that the incidence of AS has jumped from 0.3% to 3% among patients with IBD. However, these findings do not definitively establish a causal relationship whereby IBD directly leads to the development of AS. Moreover, whether the activity of IBD will have an impact on this process remains a pending question. Methods: Two-sample Mendelian randomization (MR) analyses were employed across multiple datasets to investigate the potential of IBD as a risk factor for AS. The pathogenic genes of AS were identified by MR analysis of expression quantitative trait locus. Risk scores for active and inactive patients were calculated by single-sample gene set enrichment analysis. Comparative assessments encompassing alterations in risk transcription factor activity, shifts in signaling pathways, and variances in immune cell profiles were conducted between active and inactive patients. Moreover, the correlation of immune cells and risk genes was quantified. Results: A total of 6 MR analyses, conducted across 3 exposure datasets and 2 outcome datasets, consistently revealed that IBD substantially elevates the risk of AS development. The MR analysis of the two outcome datasets identified 66 and 54 risk genes, respectively. Notably, both the risk scores computed from the two distinct sets of risk genes were notably higher in active patients compared to their inactive counterparts. Discernible variations in the activity of risk-associated transcription factors were observed between active and inactive patients. In addition, three inflammatory pathways exhibited marked activation in active patients. Moreover, seven specific immune cell types, closely linked to disease activity, exhibited statistically significant correlations with the identified risk genes. Conclusion: By combining Mendelian randomization with transcriptome analysis, this study postulates IBD as a significant risk factor for AS, and further presents innovative evidence for the impact of IBD activity on the progression of AS.